2023
DOI: 10.1002/trc2.12431
|View full text |Cite
|
Sign up to set email alerts
|

Chronic GCPII (glutamate‐carboxypeptidase‐II) inhibition reduces pT217Tau levels in the entorhinal and dorsolateral prefrontal cortices of aged macaques

Shveta Bathla,
Dibyadeep Datta,
Feng Liang
et al.

Abstract: IntroductionCurrent approaches for treating sporadic Alzheimer's disease (sAD) focus on removal of amyloid beta 1‐42 (Aβ1‐42) or phosphorylated tau, but additional strategies are needed to reduce neuropathology at earlier stages prior to neuronal damage. Longstanding data show that calcium dysregulation is a key etiological factor in sAD, and the cortical neurons most vulnerable to tau pathology show magnified calcium signaling, for example in dorsolateral prefrontal cortex (dlPFC) and entorhinal cortex (ERC).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Studies have shown that inflammatory processes in the aging brain lead to phosphorylation of tau proteins in common late-onset AD. “We are able to reduce tau phosphorylation by restoring the regulatory effects that are lost with age and inflammation,” said Arnsten ( Bathla et al, 2023 ). Members of Arnsten’s lab investigated ways to reduce tau phosphorylation early in disease progression, before neurons are damaged.…”
Section: Alzheimer’s Disease-related Tau Pathological Changesmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies have shown that inflammatory processes in the aging brain lead to phosphorylation of tau proteins in common late-onset AD. “We are able to reduce tau phosphorylation by restoring the regulatory effects that are lost with age and inflammation,” said Arnsten ( Bathla et al, 2023 ). Members of Arnsten’s lab investigated ways to reduce tau phosphorylation early in disease progression, before neurons are damaged.…”
Section: Alzheimer’s Disease-related Tau Pathological Changesmentioning
confidence: 99%
“…Members of Arnsten’s lab investigated ways to reduce tau phosphorylation early in disease progression, before neurons are damaged. Specifically, they focused on the role of GCPll (glutamate carboxypeptidase-II), a brain enzyme involved in inflammation ( Bathla et al, 2023 ). This enzyme weakens the protective effect provided by mGluR3 (metabolized glutamate receptor 3), a receptor on neurons that promotes higher cognitive function.…”
Section: Alzheimer’s Disease-related Tau Pathological Changesmentioning
confidence: 99%
See 3 more Smart Citations